A Study On Perception Of Illness And Health Seeking Behaviour Among Community In Selected Villages In Samarahan District - Haironi, Y.; Zainab, T.; Aye, A.A; Khatijah, Y. (Universiti Malaysia Sarawak, 2014)
In order to determine the health seeking behaviour and perception of illness among 4 selected villages in Samarahan, a cross-sectional study was conducted. The selected villages were Kampung Tanjong Bundong (39), Kampung Baru (39), Kampung Niup (41) and Kampung Tanjong Parang (38). Perception score was calculated based on a questionnaire consisting of 11 questions, ranging from balanced diet, physical activity, immunization, antenatal follow-up, pap smear, breast self examination, promiscuity, alcohol intake, substance abuse, cigarette smoking and perception on general health. The second part of the questionnaire was on health seeking behaviour on traditional medicine practices, vitamin intake, treatment preference and beliefs. Results showed that 76 respondents (48.4%) preferred government health centres and 48 (30.6%) respondents self-medicate while others preferred going to private clinics, pharmacy or traditional medication. The majority of the respondents (108) took traditional medicine comprising of herbal medicine (36.3%), medicinal oil (15.3%) or medicinal plants (14%). Of the total, 89 respondents (56.7%) believed that illness is due to causes other than microorganisms. A total of 121 (77.1%) respondents believed that seeking health treatment is only necessary when one is unwell. When the perception scores were tabulated, 104 respondents (66.2%) had good perception on health. It was noted that those taking vitamin supplements had better perception than those not taking (χ=9.81, df = 1, p=0.002). Males were also noted to be more likely to believe that illness is due to causes other than microorganisms. Results of this study may help to shed some light on improving health seeking behaviour among the community. This is because although the perception of health may be good, their health seeking behaviour may still be affected by cultural influence of traditional beliefs and practices